Ngukok tradition; A smoking habit in Kubang village - Agustin Wela Sasih; Azwar Ananda; Afriva Khaidir (Fakultas Ilmu Pendidikan UNP)
Ngukok tradition is smoking habit performed by young boys on Idul Fitri and Idul Adha in Kubang village. On that day, boys with a happy feeling buying and smoking a cigarette. Their parents also allow their children to smoke. While children should be avoided from smoking habits because the childhood is the period to grow and develop. This research was aimed to describe the values in ngukok tradition. This research used qualitative approach. Research was conducted in Kubang Village, Depati VII District , Kerinci Regency, Jambi Province. Total informants were 31 people selected by using purposive sampling.The techniques of data collection were observation, interview, and documentation. The data were analysed by using Miles and Huberman analysis. The research findings revealed the values contained in Ngukok tradition.Social value , such as togetherness, solidarity, silaturrahmiand mutual sharing.Religious value, such as expressing gratitude to God and fasting. Cultural value which is related to cultural inheritance.